ANALISIS PENGARUH INDEKS HARGA PASAR SAHAM DUNIA TERHADAP INDEKS HARGA PASAR SAHAM INDONESIA PERIODE 2008â2012 - Malinda, Istiqomah (Universitas Jambi, 2014)
The main pourpuse of this research is to analyze the effect of world stock priceÂ indices toward the Indonesian stock price index. World stock price indices is represented by four global indices:Â Nikkei 225 index (Asia), the NYSE index (Amerika), FTSE index (Europe) and ASX index (Australia).Â This study utilized linear regression analysis. Data for this research was the monthly stock price index. The results of this study prove that simultaneously the Indonesia stock price index (IHSG) is significant influenced by Nikkei 225 index, the NYSE index, FTSE index and ASX index. Furthermore, partially the results show that onlyÂ Nikkei 225 index and the NYSE index have a significant effect to the Indonesia stock price index. Among the four global indices, NYSE index has a dominance effect. The study suggests for investors orpotential investors to diversify their fund into an international portfolio. Future studies may add to the index of other countries.